Strategi Pengelolaan Keuangan untuk Meningkatkan Efisiensi Pemanfaatan Peralatan Medis - Tharik Akbar; Erliany Syaodih; Rinawati Rinawati (Journal Of Business, Finance, and Economics (JBFE), 2025)
The Corporate Clinic of PT Well Harvest Winning AR in West Kalimantan faces budget constraints in the procurement and utilization of medical equipment, while the demand for healthcare services for employees and their families continues to increase. This situation requires management to develop financial management strategies that can reduce costs without compromising service quality. This study aims to formulate financial management strategies oriented toward efficiency in the utilization of medical equipment, covering cost planning, asset life cycle analysis, maintenance, and financing schemes based on the value for money principle. The research employed a qualitative descriptive method with a case study approach, using interviews, observations, and document reviews related to financial records and equipment maintenance logs. The findings indicate that implementing life cycle cost analysis (LCCA), performance-based service contracts (SLA), equipment utilization optimization, and improving staff competencies are effective strategies to reduce operational costs, maintain service quality, and enhance the efficiency of medical equipment utilization in the corporate clinic.